IgG antibody responses to Plasmodium falciparum merozoite antigens in Kenyan children have a short half-life. - Kinyanjui, S; Conway, D; Lanar, D; Marsh, K (BioMed Central, 2007)
BACKGROUND: Data suggest that antibody responses to malaria parasites merozoite antigens are generally short-lived and this has implications for serological studies and malaria vaccine designs. However, precise data on the kinetics of these responses is lacking. METHODS: IgG1 and IgG3 responses to five recombinant Plasmodium falciparum merozoite antigens (MSP-119, MSP-2 type A and B, AMA-1 ectodomain and EBA-175 region II) among Kenyan children were monitored using ELISA for 12 weeks after an acute episode of malaria and their half-lives estimated using an exponential decay model. RESULTS: The responses peaked mainly at week 1 and then decayed rapidly to very low levels within 6 weeks. Estimation of the half-lives of 40 IgG1 responses yielded a mean half-life of 9.8 days (95% CI: 7.6-12.0) while for 16 IgG3 responses it was 6.1 days (95% CI: 3.7-8.4), periods that are shorter than those normally described for the catabolic half-life of these antibody subclasses. CONCLUSION: This study indicates antibodies against merozoite antigens have very short half-lives and this has to be taken into account when designing serological studies and vaccines based on the antigens.